A study of fungal corneal ulcer - Meena, Vandana; Sharma, Unnati (International Journal of Medical Research and Review, 2016)
Background: Fungal keratitis is an inflammation of the cornea caused by fungi. This infection is difficult to treat and it can lead to severe visual impairment or blindness. It is worldwide in distribution, but is more common in the tropics and subtropical regions. Corneal ulcers are the second most-common cause of preventable blindness after cataract in tropical developing countries. Material & Methods: A retrospective study included 30 cases of fungal corneal ulcer was carried out on indoor and outdoor cases of fungal corneal ulcer, in Department of ophthalmology, in technical collaboration with department of microbiology in tertiary care teaching hospital. A presumptive diagnosis was based on clinical features and history, diagnosis was confirmed by KOH preparation and culture. Results: The maximum incidence of ulcers was seen in age group of 41-60 years and majority of them were males. Most common predisposing factor was trauma. Most common clinical feature was slough followed by hypopyon, perforation, lowered intraocular tension, satellite lesions and vascularization respectively. Conclusion: The diagnosis of fungal keratitis is usually difficult. The clinical suspicion by ophthalmologist is unequivocally, key element in making diagnosis of fungal infection of cornea. A wide range of conventional and molecular techniques are currently available for laboratory diagnosis of fungal keratitis. Early diagnosis and appropriate treatment are essential to avoid blindness.